Behavior and microstructural changes in different tungsten-based materials under pulsed plasma loading. (December 2016) - Vilémová, M.; Pala, Z.; Jäger, A.; Matějíček, J.; Chernyshova, M.; Kowalska-Strzęciwilk, E.; Gribkov, V.A.; Janata, M.
Highlights: Minor erosion mechanism related to inherent porosity of sintered materials described. Degradation of promising plasma facing material W-Y2O3 described–formation of Y2O3 layer on the surface, depletion layer. Important note on phase stability of W-Y2O3 was made–possible transition to high pressure B phase. Abstract: In this study, morphological, microstructural and phase changes of four types of tungsten materials after exposure to dense deuterium plasma were examined. The microstructures of the prepared materials mutually differ by the porosity, grain size and phase content. It was found that inherent porosity of sintered materials leads to a specific mechanism of erosion and might be a significant source of dust in the case of materials with higher porosity. Further, a preferential erosion of the dispersed particles by melting and evaporation and subsequent formation of thin film on the surface of W-Y2 O3 was described as well.